High temperature behavior of calcium aluminate cement pastes (2020)
ABSTRACT: Calcium aluminate cements (CAC) are important materials today, as they cover a good number of applications in civil engineering, refractory industry and materials science, which is mainly due to their excellent high temperature mechanical properties, strength to corrosion, erosion wear, among others. The inherent brittleness and lack of ductility of these cements, particularly make them susceptible to failures mainly by thermal shock and slow outflow. In order to understand and elucidate the micro mechanisms that govern outflow damages and / or high temperatures, it is necessary to know the high temperature behavior of calcium aluminate cement pastes, the transformations of their phases, and their types and mechanisms of damage, complex phenomena related to factors such as chemical composition, water / cement ratio and alumina content. Calcium aluminate cements are the basis for the manufacture of many refractory ceramics, advanced ceramics, and functional materials with gradients used in many different applications. Therefore, this proposal is intended to contribute to the understanding of the behavior of pure calcium aluminate cement paste and added with silica, for different alumina contents, subjected to high temperatures and using different water/cement ratio (W/C). In order to improve knowledge in this topic, once the calcium aluminate cement paste samples have been manufactured, they were exposed to high temperatures and analyzed using techniques such as scanning electron microscopy, infrared transformation spectroscopy of Fourier, X-ray diffraction, X-ray fluorescence, among others. Then, to be able to establish mathematical models that allow the damage to be quantified and the micro-mechanisms that govern this behavior to be revealed.